2017
DOI: 10.1021/acs.jpclett.7b01599
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Complex Vibrational Spectrum of the Protonated Water Trimer, H+(H2O)3, with Two-Color IR-IR Photodissociation of the Bare Ion and Anharmonic VSCF/VCI Theory

Abstract: Vibrational spectroscopy of the protonated water trimer provides a stringent constraint on the details of the potential energy surface (PES) and vibrational dynamics governing excess proton motion far from equilibrium. Here we report the linear spectrum of the cold, bare H(HO) ion using a two-color, IR-IR photofragmentation technique and follow the evolution of the bands with increasing ion trap temperature. The key low-energy features are insensitive to both D tagging and internal energy. The D-tagged D(DO) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(114 citation statements)
references
References 55 publications
10
97
0
Order By: Relevance
“…It should be noted that our work does not aim to improve the current physical understanding of the reaction but instead has chiefly a modeling integration objective. Our results integrates the findings of the work of Geissler et al 22 For an improved physical description of the proton transfer mechanisms, path sampling shall be used with more recent models such as improved SD, 23 density functional theory, 24 Møller‐Plesset perturbation theory, 25 vibrational motion 26,27 and finally, the Neural Network Potentials at Coupled Cluster Accuracy 28 …”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…It should be noted that our work does not aim to improve the current physical understanding of the reaction but instead has chiefly a modeling integration objective. Our results integrates the findings of the work of Geissler et al 22 For an improved physical description of the proton transfer mechanisms, path sampling shall be used with more recent models such as improved SD, 23 density functional theory, 24 Møller‐Plesset perturbation theory, 25 vibrational motion 26,27 and finally, the Neural Network Potentials at Coupled Cluster Accuracy 28 …”
Section: Introductionsupporting
confidence: 78%
“…This has been claimed to generate large deviations in the rate computation when considering reduced dimensionality approaches 46 . This vibration can be mapped, as an independent degree of freedom, in the initial and final stable states, as well as during the reaction since it can induce a Fermi resonance 26,27 that might significantly alter the reaction dynamic. To assert if the hydrogen distances correlate with the reaction, classifiers can be employed.…”
Section: Proton Transfer In the Protonated Water Trimermentioning
confidence: 99%
“…In addition, the confined cations have a shoulder before the conventional asymmetric N–H stretching vibrational peak at 3344 cm –1 . Above vibrational spectra are different from those of other interfaces such as EAN–air, EAN–carbon nanotube, and water–Au nanoparticle. , Some previous works , have confirmed that the characteristic asymmetric stretching vibration peak of N–H at 3344 cm –1 is due to HBs between EAN ion pairs. For the EAN IL molecules confined inside the TiO 2 slits, the EA + cations can form two types of HBs: one with the TiO 2 wall and the other with the NO 3 – anions.…”
Section: Results and Discussionmentioning
confidence: 85%
“…27 Other values of n reveal structures in between the limiting Eigen and Zundel configurations. 26,28 Spectroscopic insights that inform our understanding of the hydrated proton have resulted from a bottom-up approach of investigating PWCs of increasing size. Because the clusters are cold, the IR spectra contain relatively sharp features that are amenable to interpretation in terms of specific configurations and vibrational modes, in contrast to the mostly featureless continuum of the fully hydrated proton in aqueous solution.…”
mentioning
confidence: 99%